Craniopharyngioma in a young woman with symptoms presenting as mechanical neck pain associated with cervicogenic headache: a case report. (3rd April 2021) - Mourad, Firas; Cataldi, Fabio; Patuzzo, Alberto; Tunnera, Sara; Dunning, James; Fernández-de-las-Peñas, César; Maselli, Filippo
ABSTRACT: Background : Craniopharyngioma is benign neoplasm thought to be caused by mal-development, which occurs in both children and adults in the sellar and suprasellar regions of the brain. Typical manifestations in adults are visual and endocrine system symptoms followed by signs and symptoms of increased intracranial pressure (i.e., headache). The management of this rare condition is complex and requires life-long surveillance by a multidisciplinary team of health-care professionals. Objective : To present a rare clinical presentation of craniopharyngioma mimicking nonspecific neck pain usually associated with cervicogenic headache recognized by a physiotherapist in a direct access setting as a condition requiring medical referral. Case Presentation : This case report describes the history, examination findings, and clinical reasoning used in the initial examination of a 33-year-old female with neck pain and cervicogenic headache as chief complaints. Several key indicators in the patient presentation warranted further and urgent investigation: 1) the recent onset of a "new-type" headache; 2) the phenotype headaches change; 3) the rapid progression of the symptoms; 4) the presence of associated neurological signs and symptoms; and 5) the worsening of the symptoms during Valsalva-like activities. The decision was made to refer the patient for further evaluation. An MRI revealed a craniopharyngioma. After a surgical removal of the tumor mass, the patient participated in a rehabilitation program and reached a full recovery after 6 months. Conclusion : This case report highlights the need of more research regarding red flags and warning signs during examination of in the head-neck region, and the central role of primary care clinicians such as physiotherapists in differential diagnosis of life-threatening conditions.